Nursing and midwifery regulation and HIV scale-up: establishing a baseline in east, central and southern Africa - McCarthy, Carey F (International AIDS Society, 2013)
INTRODUCTION: Shifting HIV treatment tasks from physicians to nurses and midwives is essential to scaling-up HIV services in sub-Saharan Africa. Updating nursing and midwifery regulations to include task shifting and pre-service education reform can help facilitate reaching new HIV targets. Donor-supported initiatives to update nursing and midwifery regulations are increasing. However, there are gaps in our knowledge of current practice and education regulations and a lack of information to target and implement regulation strengthening efforts. We conducted a survey of national nursing and midwifery councils to describe current nursing and midwifery regulations in 13 African countries. METHODS: A 30-item survey was administered to a convenience sample of 13 national nursing and midwifery regulatory body leaders in attendance at the PEPFAR-supported African Health Profession Regulatory Collaborative meeting in Nairobi, Kenya on 28 February, 2011. The survey contained questions on task shifting and regulations such as registration, licensure, scope of practice, pre-service education accreditation, continuing professional development and use of international guidelines. Survey data were analyzed to present country-level, comparative and regional findings. RESULTS: Task shifting to nurses and midwives was reported in 11 of the 13 countries. Eight countries updated their scope of practice within the last five years; only one reported their regulations to reflect task shifting. Countries vary with regard to licensure, pre-service accreditation and continuing professional development regulations in place. There was no consistency in terms of what standards were used to design national practice and education regulations. DISCUSSION: Many opportunities exist to assist countries to modernise regulations to incorporate important advancements from task shifting and pre-service reform. Appropriate, revised regulations can help sustain successful health workforce strategies and contribute to further scale-up HIV services and other global health priorities. CONCLUSIONS: This study provides fundamental information from which to articulate goals and to measure the impact of regulation strengthening efforts.